The age of analysis : 20th century philosophers (The Mentor philosophers., 1955)
Basic writings of Henri Bergson, Charles Sanders Peirce, Alfred North Whitehead, William James, Benedetto Croce, Bertrand Russell, Ludwig Wittgenstein, George Santayana, John Dewey, Jean Paul Sartre, and others.